Assessment of Ambient Particulate Matter Concentrations- PM10, PM2.5 and PM1 at Rinchending in Phuentsholing, Bhutan - Humagai, Bharat Kumar; Adhikari, Kirtan; Pradhan, Basant; Yangzom, Tshering (Bhutan Journal of Research and Development, 2022)
This paper presents the analysis and interpretation of daily, monthly and seasonal cycle of 1- minute average Particulate Matter (PM10, PM2.5 and PM1) concentrations measured in Rinchending, located on the hilltop, 4 km away from Phuentsholing, the second largest city in Bhutan between the period of March 2018 to March 2019. In diurnal cycle, the highest concentrations of PM were observed between 9AM – 10 AM in the morning and 5PM-7PM in the evening corresponding to the peak traffic hours. The concentrations of PM showed highest in the post-monsoon season, corresponding to October to February in Bhutan (PM10=57.36 μg/m3, PM2.5=33.73 μg/m3 and, PM1=29.28) compared to monsoon season corresponding to June-September (PM10=22.70 μg/m3, PM2.5=15.51 μg/m3 and, PM1=11.35) and pre-monsoon season corresponding to March-May (PM10=54.9 μg/m3, PM2.5=30.58 μg/m3 and, PM1=24.36). The frequency distribution of PM10 showed that upto 25% of the time, the concentration was upto 20.8 μg/m3, 50% of the time, the concentration was upto 35.3 μg/m3 and 75% of the time, the concentration was upto 59 μg/m3.Similarly, the frequency distribution of PM2.5 showed that upto 25% of the time, the concentration was upto 13.5 μg/m3, 50% of the time, the concentration was upto 22 μg/m3 and 75% of the time, the concentration was upto 38 μg/m3.The annual mean concentrations of PM10 (45.08 μg/m3) were violating the Annual WHO ambient air quality standard (20 μg/m3). The annual mean concentrations of PM2.5 (26.83μg/m3) were also violating the Annual WHO ambient air quality standard (10 μg/m3). The wind analysis done through the wind rose diagram found a dominant south and south-west wind pattern.